1992
DOI: 10.1111/j.1365-4362.1992.tb01383.x
|View full text |Cite
|
Sign up to set email alerts
|

ENALAPRIL: A POWERFUL IN VITRO NON‐THIOL ACANTHOLYTIC AGENT

Abstract: Drugs containing sulfhydryl groups (thiol drugs) (e.g., penicillamine, captopril, thiopronine) can induce pemphigus in vivo and provoke acantholysis in vitro. Enalapril, like captopril, is an angiotensin-converting enzyme (ACE) inhibitor largely used as an antihypertensive drug; it has recently been reported to induce pemphigus, though it is not a thiol drug. In this study we investigated the possible in vitro acantholytic effect of enalapril on normal human skin from donors. The drug induced severe acantholyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…In fact, the prolonged administration of enalapril induced acantholysis in our patient (of which, however, there was no clinical evidence) as it also happens in normal human skin cultures after exposure to this drug [1, 6, 7]. The acantholytic effect was probably of a biochemical type (inhibition of epidermal transglutaminases), and not of an immune type as proven by the absence of fixed IC antibodies (DIF was negative).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In fact, the prolonged administration of enalapril induced acantholysis in our patient (of which, however, there was no clinical evidence) as it also happens in normal human skin cultures after exposure to this drug [1, 6, 7]. The acantholytic effect was probably of a biochemical type (inhibition of epidermal transglutaminases), and not of an immune type as proven by the absence of fixed IC antibodies (DIF was negative).…”
Section: Discussionmentioning
confidence: 95%
“…The acantholytic potential of this drug, a non-thiol antihypertensive ACE inhibitor, has repeatedly been proven in vitro [1, 6, 7]. It was indeed demonstrated that enalapril can induce acantholysis in vitro at already 1.5 m M , i.e.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In particular, enalapril, a nonthiol drug, which in vitro shows an acantholytic potential tenfold greater than captopril [22], can in vivo induce true pemphigus [19]or even a subclinical form of the disease [23]. …”
Section: Drug Intakementioning
confidence: 99%